The potential roles of T-type Ca2+ channels in motor coordination - Park, Young-Gyun; Kim, Jeongjin; Kim, Daesoo (Frontiers in Neural Circuits, 2013)
Specific behavioral patterns are expressed by complex combinations of muscle coordination. Tremors are simple behavioral patterns and are the focus of studies investigating motor coordination mechanisms in the brain. T-type Ca2+ channels mediate intrinsic neuronal oscillations and rhythmic burst spiking, and facilitate the generation of tremor rhythms in motor circuits. Despite substantial evidence that T-type Ca2+ channels mediate pathological tremors, their roles in physiological motor coordination and behavior remain unknown. Here, we review recent progress in understanding the roles that T-type Ca2+ channels play under pathological conditions, and discuss the potential relevance of these channels in mediating physiological motor coordination.